(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
To grab the consumer base, marketers are devising strategies to integrate their advertising and marketing campaigns across multiple channels. Among these channels of marketing, social media continues to be the most preferred marketing tool. The objective of this paper is to study the impact of social media on consumer buying decisions, considering brand equity and brand loyalty in relation to electronic home appliances. In the present study, 497 respondents are collected through self-structured questionnaires. A model has been developed and tested using structural equation modeling. Thus, the study makes a significant contribution that will be helpful for marketers to improve the quality of their products and attain maximum consumer satisfaction. It is found that brand equity and brand loyalty have both direct and indirect impact through social media marketing on consumer buying intentions.